INVESTIGATION OF PRE-SERVICE TEACHERS' AWARENESS OF STEM AND STEM TEACHING INTENTION - Aydogan Yenmez, Arzu; Gökce, Semirhan; Aydede, Meryem Nur; Çelik, Tugba (International Online Journal of Education and Teaching, 2020)
STEM education is the interdisciplinary application of knowledge and is designed around collaborative efforts to provide students with comprehensive, meaningful and unique learning experiences. For an effective STEM education, the role of teachers is very important. Through teachers who know STEM education, they would be able to handle different disciplines in an integrated way. In order to achieve the objectives related to STEM education, teachers who have sufficient knowledge and skills regarding STEM education are needed. In this sense, the awareness and intention of pre-service teachers have a very important place. In this research, pre-service teachers' awareness status and intention towards STEM education were examined. The participants of the research are 192 pre-service teachers studying in Computer Education and Instructional Technology, Science Education, Elementary Mathematics Education and Turkish Language Education programs. The one group pre-test post-test design was used in this study. The results of this study revealed the intention and awareness of pre-service teachers towards STEM education. The pre-service teachers' intention and awareness of this education shows that the teachers who adopt STEM education, who use the activities in their lessons, and who are interested in interdisciplinary knowledge acquisition, can take place in Turkish education system.